The use of robots for delivery of packages in food industries and its impact on job loss - Naser, Yaqubi; Abubakar Ibrahim, Adamu (IIUM Journal, 2022)
Artificial intelligence (AI) and robotics have developed rapidly in the last few years, both in terms of the resources and outputs they produce. The robots that work in the food industry contribute significantly to the transportation of food packages from one location to another. The main task of the robots in the food industry on which this research focuses is delivery of packages. Before the implementation of robots in food industries and in delivery packages, it was done by human beings. Now that the robots are utilised, human beings will lose their jobs. This might not necessarily be the case or there might besome unforeseen issues. That is why this research aims to investigate the influence of system quality, information quality, and business value on the delivery of packages by robots in replacing people's jobs. This study applied a quantitative research method in order to achieve all of the research objectives. A total of 310 participants took part in the survey. Based on PLS-SEM analysis, the path coefficient of system quality to business value was examined by hypothesis one (H1), and it was shown to be supported. It is clear that the relationship between system quality and business value is significant because there is a strong link between system quality and business value. Furthermore, the path coefficient of information quality to business value was investigated in hypothesis two(H2). Our second hypothesis is supported by the p-value being significant and positive. Hypothesis three(H3)is significant, as evidenced by the fact that it is supported. As a result, there are important connections between the use of robots and business value. Finally, the business value, which is a dependent variable, has a positive and significant relationship with all independent variables of this research. There is a strong path coefficient link from business value to system quality, information quality, and the use of robots. In the measurement model, there are substantial disparities between the industries with highlevels of working experience and those with less working experience of robots. Information quality, use of robots, and business value all have positive and significant influences on the use of robots in the food industry (delivery of packages by robots). Furthermore, the analyses of PLS-SEM also show that system quality has a positive relationship but not a significant impact. Technological skills are highly important in order to improve and adopt delivery of packages by robots in the food industry. In addition, the findings of this research contribute to the literature on robots’implementation in the food industry and also contribute to limited empirical research on assessing the delivery packages by robots in food industries on replacing people's jobs.